Disruptive behaviors among nurses in Israel - association with listening, wellbeing and feeling as a victim: a cross-sectional study - Sigal Shafran Tikva; Avraham N. Kluger; Yulia Lerman (BMC, 2019)
Abstract Objectives To examine the association between listening and disruptive behaviors and the association between disruptive behavior and the wellbeing of the nurse. To test whether constructive and destructive listening has an incremental validity. Methods A structured questionnaire survey that measured the (constructive & destructive) listening climate at work, exposure to disruptive behaviors, well-being and feeling as a victim. We presented this survey using the Qualtrics software. Results Of the final sample of 567 respondents who reported that they were nurses, MAge = 38.41, 67% indicated that they were exposed to some form of disruptive behavior. Experiencing listening in the ward was associated with low levels of exposure to disruptive behaviors; exposure to disruptive behaviors, in turn, predicted reduction in the nurses' wellbeing; the reduction in wellbeing was especially pronounced among nurses who felt like a victim. Each of the facets of the listening measure-constructive listening and destructive listening-had incremental validity in predicting exposure to disruptive behaviors. Finally, the effect of exposure to disruptive behavior on wellbeing was curvilinear. Conclusions Disruptive behavior is a major challenge to the workplace well-being for nurses. The victim mentality has an adverse impact on nurses. Preventive efforts aimed at reducing disruptive behaviors among nurses and decreasing their sense of victimization are crucial for the well-being of nurses.